Pengaruh Preferensi Dan Motivasi Terhadap Kepuasan Pengunjung Gen Z Di Museum Macan - Ulfi Maranisya; Rasya Maulida Rahma (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to evaluate the influence of preferences and motivation on the level of satisfaction of visitors, especially Gen Z at the MACAN Museum. The data analysis method used in this research is quantitative descriptive analysis. Through regression model analysis, several significant conclusions can be drawn. First, a constant value of 3.168 implies that if the preferences and motivation of visitors to the MACAN Museum is 0, then the level of visitor satisfaction is 3.168. Second, the regression coefficient for variable X1 of 0.070 indicates that preferences have a positive impact on the level of visitor satisfaction, while third, the regression coefficient for variable has a positive and significant impact on Generation Z Visitor Satisfaction (Y) at the MACAN Museum